Antimicrobial potential of Kaffir Lime (Citrus hystrix D.C) peel extract against Staphylococcus aureus - Kanti Ratnaningrum; Ginda Nabila Choirunnisa; Ika Dyah Kurniati (Saintika Medika, 2022)
Staphylococcus aureus is a normal bacterial flora that can cause skin infections such as boils, acne, impetigo and is also a major cause of nosocomial infections. This study examined the effect of kaffir lime (Citrus hystrix D.C) peel extract on Staphylococcus aureus. This research was a true experimental study with a post test only control group design. Kaffir lime peel was extracted using maceration method with 70% ethanol solvent, then diluted using 2ml ethanol to a concentration of 25mg/ml, 20mg/ml, 15mg/ml, 10mg/ml and 5mg/ml. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were conducted to assess the kaffir lime peel extract against Staphylococcus aureus bacteria. The MIC test was measured using a spectrophotometer in the liquid dilution method and MBC test was carried out using solid dilution on Mueller Hinton media. Minimum Inhibitory Concentration of kaffir lime peel extract against Staphylococcus aureus bacteria at a concentration of 20mg / ml., while MBC in this study could not be determined because at a concentration of 25% there was still colony growth in repetitions 1 and 2.